(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2016)
Digital filters are frequency selective system which is used to pass a certain range of frequency and to stop another range of frequency. The use of a filter plays an important part in a communication channel because it is effective at eliminating spectral leakage, reducing channel width, and eliminating interference from adjacent symbols (Inter Symbol Interference) ISI. They are actually characterized by their impulse responses. Depending upon the duration of the impulse response, digital filter are classified as Finite –Duration Impulse Response (FIR) and Infinite Duration Impulse Response (IIR) filters. Different techniques have been used for the design of FIR filter, which includes window based method frequency sampling method and various evolutionary algorithms are also being used for this purpose. The use of different optimization technique, such as Genetic Algorithm (G.A.), Particle Swarm Optimization (PSO) has been proved to be quite useful towards the design of these digital filters with certain specification. But using D.E. algorithm low pass FIR filter are also quite possible. D.E. Algorithm is better than other algorithms